2005
DOI: 10.1097/01.hp.0000142501.96410.ef
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cancer Thyroid Diseases Among Children in the Kaluga and Bryansk Regions of the Russian Federation Exposed to Radiation Following the Chernobyl Accident

Abstract: This paper presents results of estimated radiation risks of non-cancer thyroid diseases in the people from Kaluga and Bryansk regions of the Russian Federation exposed in their childhood to radioiodine as a result of the Chernobyl accident. This work was carried out under the Joint Medical Research Project on non-cancer thyroid diseases conducted by Sasakawa Memorial Health Foundation and the Medical Radiological Research Center of the Russian Academy of Medical Sciences. The subjects were 2,457 people who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the next 10–20 years after the accident, the first study, undertaken from 1997 to 1999 (at 11–13 years after the accident) [ 31 ] showed no significant radiation dose–response of chronic thyroiditis as determined by thyroid ultrasound examination. In the second study, anti-thyroid antibodies as well as thyroid hormones and TSH were measured in sera collected from 1999 to 2001 (at 13 to 15 years after the accident) [ 32 ].…”
Section: The Effect Of Moderate- To Low-dose Radiationmentioning
confidence: 99%
“…In the next 10–20 years after the accident, the first study, undertaken from 1997 to 1999 (at 11–13 years after the accident) [ 31 ] showed no significant radiation dose–response of chronic thyroiditis as determined by thyroid ultrasound examination. In the second study, anti-thyroid antibodies as well as thyroid hormones and TSH were measured in sera collected from 1999 to 2001 (at 13 to 15 years after the accident) [ 32 ].…”
Section: The Effect Of Moderate- To Low-dose Radiationmentioning
confidence: 99%
“…Given that the effect we observed was highly non-linear and seen only at the lowest doses, it could easily be overlooked when specific thresholds for thyroid volume are applied to make the diagnosis of enlarged thyroid or diffuse goiter. The fact that some studies showed no effect [ 12 , 17 ], while others found a positive association between 131 I exposure and diffuse goiter [ 13 , 18 ] is therefore unsurprising, and may also reflect low statistical power in some of these studies. Because our study focuses solely on thyroid volume rather than on a diagnosis of thyroid enlargement or diffuse goiter, we were able to detect even weak signals in the data that might otherwise be obscured.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this is the first study to examine association between 131 I dose to the thyroid gland and thyroid volume in a population of individuals exposed during childhood and systematically screened 10-15 years later. Previous studies had much more limited information on thyroid volume [ 18 ] or dose [ 11 15 ]. Our study adds to the current literature by providing evidence for a moderate statistically significant increase in thyroid volume among those who were 18 years or older 10-15 years after the accident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association was modest and best described by several concave models. In a similar study of Russian children exposed to Chornobyl fallout who had measurement-based individual thyroid doses, there was no evidence of a dose-response relationship for autoimmune thyroiditis that was diagnosed by ultrasound and confirmed by TSH and ATPO measurements 11–13 years after the accident (65). The authors did not evaluate the dose-response relationship for ATPO prevalence separately because ATPO measurements were not available for all study participants.…”
Section: Thyroid Diseasesmentioning
confidence: 99%